2021
DOI: 10.4103/cjp.cjp_13_21
|View full text |Cite
|
Sign up to set email alerts
|

Adropin and Spexin Hormones Regulate the Systemic Inflammation in Adenine-Induced Chronic Kidney Failure in Rat

Abstract: Chronic kidney disease is one of the major global health problems. Chronic renal failure is stimulated by many cytokines and chemokines. Adropin and spexin (SPX) are peptides hormones. These peptides could affect inflammatory conditions, but this is unclear. Due to the limited information, we planned to investigate the impact of adropin and SPX hormones on systemic inflammation in adenine induced chronic kidney failure rat model. Chronic kidney failure was induced by administering adenine hemisulfate. Renal fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…Although adropin has been previously investigated in numerous animal and clinical studies as a biomarker of T2DM-induced nephropathy, endothelial dysfunction, arterial stiffening, and atherosclerosis [ 24 , 47 , 48 , 49 ], there are scarce studies regarding its predictive ability in the HF population with several concomitant diseases, including T2DM and obesity [ 50 ]. Accumulating data suggest that adropin exerts metabolic regulation of gluconeogenesis, ketone production, and lipid oxidation in the myocardium, liver, and skeletal muscle [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although adropin has been previously investigated in numerous animal and clinical studies as a biomarker of T2DM-induced nephropathy, endothelial dysfunction, arterial stiffening, and atherosclerosis [ 24 , 47 , 48 , 49 ], there are scarce studies regarding its predictive ability in the HF population with several concomitant diseases, including T2DM and obesity [ 50 ]. Accumulating data suggest that adropin exerts metabolic regulation of gluconeogenesis, ketone production, and lipid oxidation in the myocardium, liver, and skeletal muscle [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study demonstrated that adropin expression in lung tissue and serum in AP-ALI models ws decreased, supporting the likelihood of its involvement in the progression of AP-ALI. Adropin can regulate renal function and inflammatory responses, exerting a protective effect on the progression of systemic inflammation and renal failure ( 15 ). Adropin has been shown to inhibit inflammation by reducing the levels of pro-inflammatory cytokines and IL-6 in tissues ( 16 ).…”
Section: Discussionmentioning
confidence: 99%